Investigation of Sociodemographic Characteristics, Work Life and Mental Health in Mobbing Victims: Case Series - Deniz, Derya (The Bulletin of Legal Medicine, 2019)
Objective: The aim of this study to evaluate mobbing victims who resorted to outpatient clinics of Department of Forensic Medicine at İstanbul University Faculty of Medicine. 34 workers who were exposed to mobbing were evaluated by clinical interview and social investigation. Materials and Methods: Information about the mobbing process, sociodemographic characteristics and workplace of the cases were obtained by clinical interview. In this study, the diagnoses given to the patients after the assessment in the Psychiatry Department of İstanbul University Medical Faculty were used. Descriptive Analysis were made using the data of 34 participants.Results:  67.6% of the cases were female and 32.4% were male. They were aged between 31-62 years and the mean age was 42, 18. 20 of the cases were single, 12 of them were married and 2 of them were divorced. 3 of them were high school graduates, 11 of them have bachelor’s degree and 10 of them have master’s degree. 24 of them (% 70, 6) were working in the public sector and 10 of them (%29,4) were working in the private sector. Their work experiences range from 5 to 35 years. The mean duration of exposure to mobbing was 31.6 months. 91.2% of the cases (31 workers) stated that they were exposed to vertical mobbing.16 of cases were teachers, 7 of them were academicians, 2 of them were health workers, 4 of them were employees of service sector, 2 of them were civil servants, 2 of them were non-governmental organizations’ workers and...
Keywords: Bullying; Crime Victims; Forensic Psychology; Forensic Sciences